2014
DOI: 10.1364/boe.5.003792
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone instrument for portable enzyme- linked immunosorbent assays

Abstract: We demonstrate the utilization of a smartphone camera as a spectrometer that is capable of measuring Enzyme Linked Immunosorbent Assays (ELISA) at biologically-relevant concentrations with the aid of a custom cradle that aligns a diffraction grating and a collimating lens between a light source and the imaging sensor. Two example biomarkers are assayed using conventional ELISA protocols: IL-6, a protein used diagnostically for several types of cancer, and Ara h 1, one of the principle peanut allergens. In addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
81
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(82 citation statements)
references
References 42 publications
(44 reference statements)
0
81
0
1
Order By: Relevance
“…A compact colorimetric and fluorometric reader (Mudanyali et al, 2012), as well as a CP-based compact EC sensing platform, have been reported (Lillehoj et al, 2013). Indeed, it is feasible for colorimetric readout from a 96-well microtiter plate (MTP) using a CP device (Vashist et al, 2015a, Vashist et al, 2015b and the measurement of a full emission spectrum of any light emitter using a CPbased fluorimeter (Long et al, 2014, Yu et al, 2014. Together with graphene as a sensing interface, the CP-platform doubtlessly provides cost-effective mobile healthcare and personalized medicine with widespread applications for point of care testing (POCT) (Vashist et al, 2015c).…”
Section: Immunosensing Procedures For Ceamentioning
confidence: 99%
“…A compact colorimetric and fluorometric reader (Mudanyali et al, 2012), as well as a CP-based compact EC sensing platform, have been reported (Lillehoj et al, 2013). Indeed, it is feasible for colorimetric readout from a 96-well microtiter plate (MTP) using a CP device (Vashist et al, 2015a, Vashist et al, 2015b and the measurement of a full emission spectrum of any light emitter using a CPbased fluorimeter (Long et al, 2014, Yu et al, 2014. Together with graphene as a sensing interface, the CP-platform doubtlessly provides cost-effective mobile healthcare and personalized medicine with widespread applications for point of care testing (POCT) (Vashist et al, 2015c).…”
Section: Immunosensing Procedures For Ceamentioning
confidence: 99%
“…To this end, custom solutions can be developed and paired with the devices. For instance, an example of a custom sensing solution that can detect protein and allergens is explored by Long et al [11]. Their setup allows the user to extract the physical parameters of a sample and achieve high precision fingerprinting.…”
Section: Related Workmentioning
confidence: 99%
“…With the help of 3D printers, smartphone spectrometer systems found wide range of colorimetric measurements application for chemical and biological analytes [3]. Some of them are water quality sensing for environment [4,5], leaf color analysis for agriculture [6], pH [7,8] and glucose [9] sensing, and peanut allergen detection [10]. Color data is mostly used in paper based sensors application where parameters from various color spaces, i.e.…”
Section: Introductionmentioning
confidence: 99%